TEMPORAL STUDY OF REEF FISH COMMUNITIES (2014-2018) WATER OF MESJID RAYA SUB-DISTRICT AND PEUKAN BADA, ACEH BESAR DISTRICT (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Reef fishes are the group of fish that have a high association with the coral reef ecosystem as spawning, nursery, and feeding grounds. This study aims to determine the reef fish community through the approach of abundance, diversity, uniformity, and dominance of reef fish in 2014-2018 in the waters of the Mesjid Raya Sub-district and Peukan Bada, Aceh Besar District. This research was carried out from 2014 to 2018, with research locations, there are 8 locations. Reef fish data collection was carried out using the underwater visual census (UVC). The total species of reef fish found during 2014-2018 were 115 species from 39 families. The waters of Mesjid Raya sub-district have the lowest abundance of reef fish with a number of 128 ind/ha in 2014 observations in Lhok Mee waters and the highest abundance of fish as much as 80 ind/ha in the waters of Fort Inong Balee in 2017. It is different from sub-district waters Peukan Bada has an abundance of reef fish with the lowest value of 96 ind/ha in 2014 observations in the waters of Lhok Mata Ie and reached the highest value of 2401.70 ind/ha in the same waters in 2018. Results of the average ecological index value Reef fish in the District of Mesjid Raya and Peukan Bada in 2014-2018 did not have a significant difference.